Desain Pengembangan Kurikulum Program Pendidikan Agama Islam di SMK Negeri 2 Kota Bengkulu - Eka Dianti (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
The curriculum is a learning program used by educational institutions to be applied to students. This study aims to find out about curriculum design and curriculum implementation in Islamic religious education. This study is a type of library research. This study uses a qualitative approach in understanding a phenomenon experienced by the subject or object of research, with a descriptive method in the form of words and language. This study contains a curriculum design plan related to the preparation of curriculum elements in its planning used to facilitate the development of student potential in order to achieve educational goals. About the curriculum design that exists in two dimensions, horizontal and vertical. Curriculum components are organized into several categories. As well as the classification of curriculum design as a modification or combination of three main categories: subject-centered design, learner-centered design, and problem-centered design. In its application, the design of curriculum development, especially Islamic Religious Education in schools or madrasas, experiences paradigm changes. The curriculum is designed and developed based on the needs, interests, and talents of students, by considering the psychological aspects of students. Therefore, the design of the Islamic religious education curriculum must be designed and implemented as effectively as possible to make it easier for students to learn.